Limites, Continuidade, Derivabilidade e Aplicações - Gonçalo, Rildo Cariri (2013)
The text on Limits, Continuity, Derivability and Applications is aimed at students of undergraduate courses in mathematics and basic education teachers, especially those active in high school as a way to aid in their studies in subjects that address the differential calculus. Whenever possible, approach the issues presented with content of basic education seeking a link between some content. The examples are as clear as possible, because the goal here is not to present challenges but show direct applications of key settings.